Correlation between moral distress and clinical competence in COVID-19 ICU nurses - Zohreh Kalani; Maasoumeh Barkhordari-Sharifabad; Niloufar Chehelmard (BMC, 2023)
Abstract Background Nurses' clinical competence is one of the fundamental necessities for providing safe and effective care. Moral distress, as one type of occupational stressors, can affect various aspects of clinical competence, especially under conditions of complicated medical settings such as the coronavirus disease 2019 (COVID-19) epidemic. This study was conducted with the aim of determining the relationship between moral distress and clinical competence in nurses working in COVID-19 intensive care units (ICUs). Methods The study was a cross-sectional study. A total of 194 nurses working in COVID-19 ICU affiliated to Shahid Sadoughi University of Medical Sciences, Yazd, central Iran, participated in the study. Data were collected using Demographic Information Questionnaire, Moral Distress Scale, and Clinical Competence Checklist. Data were analyzed with SPSS20 using descriptive and analytical statistics. Results The mean score of moral distress, clinical competence, and skills application were 1.79 ± 0/68, 65.16 ± 15.38, and 145.10 ± 38.20, respectively. Based on Pearson correlation coefficient, there was an inverse and significant relationship between the moral distress score and its dimensions with clinical competence and skills application (P < 0.001). Moral distress was a significant negative predictor that accounted for 17.9% of the variance in clinical competence (R2 = 0.179, P < 0.001) and 16% of the variance in utilization of clinical competence (R2 = 0.160, P < 0.001). Conclusion Considering the relationship between moral distress, clinical competence and skills application, to maintain the quality of nursing services, nursing managers can strengthen clinical competence and skills application by using strategies to deal with and reduce moral distress in nurses, especially in critical situations.